Association of C3953T transition in interleukin 1β gene with idiopathic male infertility in an Iranian population. (3rd April 2019) - Zamani-Badi, Tayyebeh; Karimian, Mohammad; Azami-Tameh, Abolfazl; Nikzad, Hossein
Abstract: In this study we investigate the association of C3953T transition single nucleotide polymorphism in the fifth exon of the interleukin 1β gene with idiopathic male infertility. In a case-control study, blood samples were collected from 230 fertile and 207 infertile men who referred to the Kashan IVF centre. Genotypes of samples at the C3953T location were determined by polymerase chain reaction-restriction fragment length polymorphism. The data showed a significant association of TT genotype (OR = 2.49, 95%CI = 1.02–6.10; p = 0.0452) and T allele (OR = 1.46, 95%CI = 1.07–1.99; p = 0.0174) with male infertility. In a subgroup analysis, we found that the TT genotype (OR = 3.28, 95%CI = 1.16–9.26; p = 0.0249) and T allele (OR = 1.63, 95%CI = 1.10–2.41; p = 0.0142) were associated with oligozoospermia. Our findings suggest that the C3953T polymorphism could be considered as a potential biomarker for a genetic diagnosis of male infertility.